2018
DOI: 10.14202/vetworld.2018.58-65
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic intestinal parasites of carnivores: A systematic review in Iran

Abstract: Aim:Parasitic infections, especially of the zoonotic-parasitic type, are the most important health, economic, and social problems in developing countries, including Iran. The aim of this study was to review systematically the available data on gastrointestinal parasites of carnivores in Iran and their ability to infect humans.Materials and Methods:Studies reporting intestinal parasites of carnivores were systematically collected from nine electronic English and Persian databases and Proceedings of Iranian para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
2
19
0
2
Order By: Relevance
“…This finding agrees with finding from Canada [27]. This is because most intestinal parasitic infections are zoonotic in nature [28].…”
Section: Resultssupporting
confidence: 92%
“…This finding agrees with finding from Canada [27]. This is because most intestinal parasitic infections are zoonotic in nature [28].…”
Section: Resultssupporting
confidence: 92%
“…This finding agrees with finding from Canada [44]. This is because most protozoa infections are transmitted from animals to humans (zoonotic) [45].…”
Section: Intestinal Parasitic Infection Among Childrensupporting
confidence: 92%
“…Taenia hydatigena was the most represented tapeworm, with around 44% of the farms being positives. A quite recent systematic review focused on the zoonotic potential linked to parasites of carnivores in Iran (50), encompassing studies from 1997 to 2015, reported that T. hydatigena was the most frequently isolated parasite in dogs, with a prevalence of around 30% out of 1,539 examined dogs. Usually, T. hydatigena represents the most common taeniid species detected worldwide in both domestic (51) and wild environment (28), where the wolf act as the main definitive host (52).…”
Section: Discussionmentioning
confidence: 99%